Streamlined percutaneous atrial septal defect closure in adults - Arı, Selma; Ari, Hasan; Can, Veysi; Çamcı, Sencer; Melek, Mehmet (The European Research Journal, 2020)
Objectives: The aim of the study to evaluate the safety and efficacy of the transthoracic echocardiography (TTE) guided secundum atrial septal defect (ASD) closure without balloon sizing, sedation or general anesthesia in adults.Methods: We retrospectively evaluated 200 secundum ASD closure patients in the tertiary cardiology center. Transesophageal echocardiography (TEE) was performed to all the patients at least one day before the intervention by the procedure operators. The patients who were closed with a cribriform device, using more than one device, with insufficient rim (